The works of vermin - Ennes, Hiron (Tor, Tor Publishing Group, 2025)
"He was sent to kill a pest. Instead, he found a monster. Enter the decadent, deadly city of Tiliard, a metropolis carved into the stump of an ancient tree. In its canopy, the pampered elite warp minds with toxic perfume; in its roots, gangs of exterminators hunt a colossal worm with an appetite for beauty. In this complex, chaotic city, Guy Moulène has a simple goal: keep his sister out of debt. For her sake, he'll take on any job, no matter how vile. As an exterminator, Guy hunts the uncanny pests that crawl up from the river. These vermin are all strange, and often dangerous. His latest quarry is different: a worm the size of a dragon with a deadly venom and a ravenous taste for artwork. As it digests Tiliard from the sewers to the opera houses, its toxin reshapes the future of the city. No sane person would hunt it, if they had the choice. Guy doesn't have a choice."--